ANALISIS ISI PESAN PERSUASIF KOMUNIKASI LINGKUNGAN DENGAN MENGGUNAKAN FEAR APPEALS PADA MEDIA SPANDUK TPS ILEGAL DI DEPOK - Amirah Husna Fairuz (2023)
This research practically aims to provide an elaboration description of the fulfillment of the persuasive fear appeals message elements written on the banners installed by DLHK Depok City around illegal polling stations in Depok City based on aspects of the Extended Parallel Process Model (EPPM) theory by Kim Witte, namely significance, susceptibility, self-efficacy, and response efficacy. In this study, a quantitative message content analysis method was used, accompanied by a descriptive method, and presented in terms of frequency and percentage. Data analysis techniques were performed using coding sheets as measuring tools which were applied to 11 units of text and nine units of illustration analyzed by two coders. The inter-coder reliability test was carried out using the Scott formula to ensure objectivity. The results of this study indicate that banners prohibiting illegal disposal of waste in Depok fulfill the elements of persuasive message fear appeals only in the illustration elements by 55.5% but do not fulfill in the text elements, which is only 36.4%. The highest fulfillment is in the elements of susceptibility of 44.4% to 55.6%, and the lowest is in the fulfillment of self-efficacy elements and response efficacy of 0% for each element. The reliability test results show a good value in each unit of analysis, so it is considered a reliable research measurement tool.